Modified ATO ceramic target material and preparation method thereof
By doping metal oxides ZnO, Bi2O3, TiO2 or Ta2O5, the sintering process is controlled to improve the density and conductivity of ATO ceramic targets, and the problems of low density of targets and poor sputtering stability in the prior art are solved, thus achieving the goal of achieving low density and poor sputtering stability. It has high density and low resistivity target materials, suitable for large-scale magnetron sputtering coating production.
Patent Information
- Application Number
- CN202411075108.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2024-12-13
AI Technical Summary
The density of existing ATO ceramic targets is difficult to reach more than 95%, resulting in frequent nodules, discharge abnormalities, powder loss and other phenomena during magnetron sputtering, which seriously restricts the development of industrialization.
By doping specific metal oxides ZnO, Bi2O3, TiO2 or Ta2O5 and controlling the sintering process conditions, the sintering density and conductivity of the target material are improved, the pores at the grain boundaries are eliminated, and the stability of the sputtering process is enhanced.
The relative density of ATO ceramic targets has been achieved at ≥97.8%, or even 99.2%, with a resistivity of ≤5.2×10-3Ω·cm, or even 3.8×10-3Ω·cm, which is stable for large-scale PVD coating. Production.
Smart Images

Figure CN119118652A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of target materials, and particularly relates to a modified ATO ceramic target material and a preparation method thereof. Background Art
[0002] The crystal structure of tin oxide (SnO2) belongs to the cubic system, and the common ones are rutile structure and tin rhombus structure. In the tin oxide crystal, the tin ion (Sn 4+ ) and oxygen ions (O 2- ) is the most important component. Tin ions are arranged in the form of face-centered cubic stacking, and oxygen ions are located at the four sides and octagonal positions of tin ions, forming strong ionic bonds with tin ions. Therefore, tin oxide crystals have a very high melting point and thermal stability. Pure tin oxide exhibits a high resistivity. When it is under high-temperature sintering conditions, it generally does not melt, but sublimates directly. When the temperature is higher than 1400°C, sublimation occurs significantly. Therefore, pure SnO2 is difficult to sinter densely, and the sintered body presents a porous, loose and low-strength structure. The density and conductivity of tin oxide ceramics are usually enhanced by doping. Common doping elements include F, Sb, V, Cu, Nb, etc.
[0003] Antimony tin oxide (ATO) film, by replacing Sn in the SnO2 lattice with Sb doping, greatly improves the conductivity of the ATO film. It has the advantages of excellent photoelectric properties, good chemical stability, and strong corrosion resistance, and is considered to be an excellent substitute for indium tin oxide (ITO) film. The preparation methods of ATO film mainly include sol-gel method, spray pyrolysis method, chemical vapor deposition method, magnetron sputtering method and pulsed laser deposition method. Among them, magnetron sputtering is a type of physical vapor deposition (PVD). It has the advantages of good coating uniformity, fast deposition rate, and easy control, and has good industrial development prospects. Therefore, the demand for high-quality ATO targets is more urgent.
[0004] The ATO target is Sb-doped tin dioxide. Antimony oxide powder and tin oxide powder are mixed, pressed into a green body, and then sintered to form a ceramic sintered body. To obtain ATO films with low resistivity and high transmittance, high-density ATO ceramic targets must be used. Target sintering methods include vacuum hot pressing sintering, spark plasma sintering (SPS), and atmospheric pressure atmosphere sintering. Vacuum hot pressing sintering and spark plasma sintering have high energy consumption and low production capacity. They are suitable for the preparation of small-sized samples and are difficult to introduce into mass production. Atmospheric pressure atmosphere sintering has mass production prospects. However, due to the non-densification mechanism in the SnO2 sintering process, the density of ATO targets has been difficult to reach more than 95% so far. During the sputtering process of the target, nodules, abnormal discharge, and powder loss often occur, which seriously restricts the development of industrialization.
[0005] Therefore, in order to further improve the density and conductivity of ATO ceramic targets, it is necessary to develop a modified ATO ceramic target that can simultaneously meet the requirements of high density and high conductivity and improve the stability of the ATO target sputtering process. Summary of the invention
[0006] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a modified ATO ceramic target and a preparation method thereof. The present invention can greatly improve the sintering density of the target, eliminate the pores between the grain boundaries, and stably be used for large-scale production of PVD coating by doping with a sintering aid and controlling the sintering process conditions while maintaining the low potential of ATO.
[0007] To solve the above technical problems, the first aspect of the present invention provides a modified ATO ceramic target, whose raw material components include, by weight: 89-98 parts of tin oxide, 1-10 parts of antimony oxide, and 1-3 parts of doped oxide, wherein the doped oxide is at least one of ZnO, Bi2O3, TiO2, and Ta2O5.
[0008] Specifically, the present invention modifies the ATO ceramic target by doping specific metal oxides ZnO, Bi2O3, TiO2 or Ta2O5, and controls the doping amount, thereby improving the sintering density of the target, eliminating the pores at the grain boundaries, and further improving the conductivity of the target and the stability during the sputtering process. Among them: ZnO, as a good sintering aid, can react with SnO2 to form a Zn2SnO4 phase, reduce internal pores, and inhibit the high-temperature volatilization and decomposition of SnO2, greatly improving the density of the sintered body. However, since the Zn2SnO4 phase is not conductive, the doping amount should not be too large. When Bi2O3 is doped, it can promote the generation of a large number of oxygen vacancies in the sintered body, and due to the presence of its liquid phase, the sintering density can be further improved. Ti 4+ With Sn 4+ At the same price, Ti is more likely to replace Sn when doped, which does not affect the conductivity of the sintered body, and generates TiSnO4 phase, which promotes sintering density. 5+ As a pentavalent ion, it can replace Sn when doped 4+ , generating a large number of free electrons, improving the conductivity of the sintered body. 5+ It is also beneficial to lower the sintering temperature of SnO2 sintered body, reduce the high-temperature volatilization of SnO2, and improve the density of the sintered body.
[0009] Preferably, the raw material components of the modified ATO ceramic target include, by weight: 94-98 parts of tin oxide, 1-7 parts of antimony oxide, and 1-3 parts of doped oxide.
[0010] Preferably, the purity of the tin oxide is ≥99.99%.
[0011] Preferably, the specific surface area (BET) of the tin oxide is 15-25 m 2 / g.
[0012] Preferably, the particle size distribution of the tin oxide is D 50 ≤0.5μm, D max ≤5μm.
[0013] Preferably, the purity of the doped oxide is ≥ 99.99%.
[0014] Preferably, the BET of the doped oxide is 15-25 m 2 / g.
[0015] Preferably, the particle size distribution of the doped oxide is D 50 ≤2μm, D max ≤10μm.
[0016] Specifically, the use of high-purity oxides can avoid the influence of impurity elements on the performance of the sintered body and promote the consistency of the density and conductive properties of the sintered body; at the same time, the use of submicron oxide powder with fine particles is conducive to promoting liquid phase sintering of the sintered body, improving the doping efficiency, and ensuring the high density of the sintered body.
[0017] The second aspect of the present invention provides a method for preparing the modified ATO ceramic target, comprising the following steps:
[0018] (1) weighing tin oxide, antimony oxide and doping oxide according to mass ratio, wet ball milling and spray drying to obtain a mixed powder;
[0019] (2) isostatically pressing the mixed powder to obtain a target blank;
[0020] (3) After degreasing the target blank, sintering it in an oxygen atmosphere to obtain the modified ATO ceramic target.
[0021] Preferably, the preparation steps of the tin oxide are: dissolving a tin salt in an alcohol solution, hydrolyzing it, and then calcining it to obtain the tin oxide.
[0022] Preferably, the tin salt comprises tin tetrachloride.
[0023] Preferably, the alcohol solution comprises ethanol, isopropanol or methanol solution.
[0024] Preferably, the calcination temperature is 500-700°C.
[0025] Preferably, in step (1), during the wet ball milling, the ball milling medium is water, and a binder and a plasticizer are added.
[0026] Further preferably, the binder includes at least one of polyvinyl alcohol (PVD), polyvinylidene fluoride (PVDF), acrylic resin, paraffin, and cellulose, and the amount of the binder is 0.4-2.5% of the total mass of the metal oxide.
[0027] Further preferably, the plasticizer comprises polyethylene glycol (PEG), and the amount of the plasticizer is 0.1-2% of the total mass of the metal oxide.
[0028] Preferably, in step (1), the moisture content of the mixed powder is ≤1%.
[0029] Preferably, in step (1), the specific surface area of the mixed powder is 15-25m 2 / g.
[0030] Preferably, in step (1), the bulk density of the mixed powder is 1.60-2.00 g / cm 3 .
[0031] Preferably, in step (2), the isostatic pressing process conditions are: isostatic pressing at a pressure of 100-200 MPa for 30-60 min.
[0032] Preferably, in step (3), the degreasing process conditions are: keeping warm at 600-650°C for 2-3 hours.
[0033] Preferably, in step (3), the degreasing is carried out in an air atmosphere.
[0034] Preferably, in step (3), the sintering temperature regime is: firstly, the temperature is raised to 1150-1250°C at a rate of 0.4-0.6°C / min, and the holding time is 6-8 hours; then, oxygen is introduced, the temperature is raised to 1350-1400°C at a rate of 0.2-0.4°C / min, and the holding time is 10-12 hours; finally, the introduction of oxygen is stopped, and the temperature is lowered to room temperature at a rate of 0.5-1.5°C / min.
[0035] Preferably, in step (3), after sintering, a grinding process is also included.
[0036] Further preferably, the grinding and cutting process comprises: firstly using an 800-mesh grinding wheel for rough grinding for 7-9 hours; and then using a 400-mesh grinding wheel for fine grinding for 7-9 hours.
[0037] The third aspect of the present invention provides the use of the modified ATO ceramic target in magnetron sputtering coating, glass furnace or battery.
[0038] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0039] The present invention adopts specific metal oxides such as ZnO, Bi2O3, TiO2 or Ta2O5 to dope and modify the ATO ceramic target, and controls the sintering atmosphere and sintering temperature system, and utilizes the characteristics of doped metal oxides and their interaction with SnO2 to improve the sintering density of the target, eliminate the pores at the grain boundary, and further improve the conductivity of the target and the stability during magnetron sputtering. The relative density of the modified ATO ceramic target is ≥97.8%, and can even reach 99.2%; the resistivity is ≤5.2×10 -3 Ω·cm, even up to 3.8×10 -3 Ω·cm. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 This is a physical picture of the modified ATO ceramic target prepared in Example 1 of the present invention;
[0041] Figure 2 The metallographic image of the modified ATO ceramic target prepared in Example 1 of the present invention;
[0042] Figure 3 This is the metallographic image of the ATO ceramic target prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0044] Example 1
[0045] A modified ATO ceramic target material comprises, by weight, 97 parts of tin oxide, 2 parts of antimony oxide and 1 part of ZnO.
[0046] A method for preparing a modified ATO ceramic target comprises the following steps:
[0047] (1) Preparation of tin oxide powder
[0048] Tin tetrachloride is dissolved in ethanol solution, hydrolyzed, and calcined at 600℃ to obtain high-purity tin oxide powder with a purity of ≥99.99% and a powder BET of 15-25m 2 / g, D 50 ≤0.5μm, Dmax ≤5μm.
[0049] (2) Preparation of mixed powder
[0050] The purity of ZnO powder is ≥99.99%, and the BET of powder is 15-25m 2 / g, D 50 ≤2μm, D max ≤10μm. The tin oxide powder, antimony oxide powder and ZnO powder prepared in step (1) are weighed according to the mass ratio and placed in a planetary ball mill for wet ball milling. The weight ratio of zirconium beads is 2:5:3, the total weight of zirconium beads is 5 times that of mixed powder, the weight ratio of water to metal oxide powder is 2:1, the rotation speed is 800rpm, the grinding time is 24 hours, and PVA and PEG are added and stirred and filtered. The amount of PVA added is 0.4-2.5% of the total mass of metal oxide, and the amount of PEG added is 0.1-2% of the total mass of metal oxide. After spray drying, the mixed powder is obtained, and the BET of the powder is measured to be 15-25m 2 / g, and its bulk density is 1.60-2.00g / cm 3 Between, moisture content ≤1%.
[0051] (3) Green billet forming
[0052] The mixed powder prepared in step (2) is injected into a cylindrical mold and then sealed. The mold is placed in an oil cylinder and subjected to cold isostatic pressing at a molding pressure of 100-200 MPa and a static pressing time of 30-60 minutes to obtain a strengthened target blank.
[0053] (4) Degreasing and sintering
[0054] The target blank obtained in step (3) is placed in a degreasing-sintering integrated furnace. The first stage is to degrease the blank. The degreasing temperature is 600-650°C, the holding time is 2-3 hours, and the atmosphere is air. After degreasing is completed, the temperature is raised to 950°C at a rate of 1°C / min and kept warm for 8 hours; then oxygen is introduced and the temperature is raised to 1200°C at a rate of 0.5°C / min, and the holding time is 6-8 hours; then the temperature is raised to 1400°C at a rate of 0.3°C / min, and the holding time is 10-12 hours; finally, the oxygen is stopped and the temperature is lowered to room temperature at a rate of 1°C / min. The sintered target barrel is added to the lathe for grinding. An 800-mesh grinding wheel is used for rough grinding and the processing is performed for 8 hours; a 400-mesh grinding wheel is used for fine grinding and the processing is performed for 8 hours to obtain the modified ATO target material of this embodiment, as shown in the physical figure. Figure 1 shown.
[0055] Figure 2 The metallographic image of the modified ATO ceramic target prepared in this embodiment is Figure 2 It can be seen that the target material has a dense structure and no obvious pores are observed.
[0056] Embodiment 2-6
[0057] Referring to the preparation method of the modified ATO ceramic target in Example 1, the difference between Examples 2-6 and Example 1 is only that the raw material components and the maximum sintering temperature of the modified ATO ceramic target are changed, as shown in Table 1.
[0058] Table 1:
[0059]
[0060] Comparative Examples 1-7
[0061] Referring to the preparation method of the modified ATO ceramic target in Example 1, the difference between Comparative Examples 1-7 and Example 1 is only that the types and amounts of raw materials of the modified ATO ceramic target, the sintering atmosphere or the maximum sintering temperature are changed, as shown in Table 2.
[0062] Table 2:
[0063]
[0064]
[0065] Performance Testing
[0066] The relative density and resistivity of the ATO ceramic targets prepared in Examples 1-6 and Comparative Examples 1-7 were tested, wherein the relative density was tested by the Archimedes drainage method, and the resistivity was tested by a resistivity meter, as shown in Table 3.
[0067] Table 3:
[0068]
[0069] As can be seen from Table 1-3, Example 1-6 adjusts the components of the doped metal oxides compared to Comparative Example 1-7, which are calculated by weight as follows: 89-98 parts of tin oxide, 1-10 parts of antimony oxide, and 1-3 parts of doped oxides, and the doped metal oxides are ZnO, Bi2O3, TiO2, and Ta2O5 respectively; the sintering atmosphere is oxygen, and the maximum sintering temperature is between 1350-1400°C. By doping with sintering-aiding metal oxides, the volatilization of tin oxide at high temperatures is suppressed, the internal pores are reduced, and sintering densification is promoted. Among them: within a certain range, the doping of zinc oxide, ZnO and SnO2 react at high temperatures to generate Zn2SnO4, fill the gaps between the particles, and greatly enhance the sintering densification of the target material. If the doping amount is too much, ZnSnO3 is easily generated, which reduces the density and conductivity of the sintered body, causing the target material to crack and delaminate during sintering, and the body resistance is significantly increased. Antimony oxide is a SnO2 doped oxide, existing in the solid solution with +3 and +5 valences. 5+ Replace Sn 4+ After that, a large number of free electrons can be provided, which effectively reduces the resistivity of tin oxide, but at the same time, a large number of lattice defects are also generated, resulting in reduced crystallinity and hindering grain growth. Therefore, a small amount of antimony oxide doping helps to reduce the resistivity of SnO2, but is not conducive to sintering densification.
[0070] Comparative Example 1 is undoped ATO, and the relative density of the target is relatively low. Metallographic microscope observation shows that there are many pores inside and the structure is relatively loose. Figure 3 As shown. In Comparative Example 2, the sintering metal oxide ZnO is over-doped, the sintered body is greatly deformed, and bulging occurs. In Comparative Example 3, the doping amount of the sintering metal oxide is insufficient, the sintering effect is not maximized, and the density still has room for improvement. Comparative Example 4 uses air atmosphere sintering, lacks the protection of oxygen atmosphere, the sintered body volatilizes more, and the density is lower. The maximum sintering temperature of Comparative Example 5 is too high, and volatilization is larger at high temperature, which also affects the density. Comparative Examples 6 and 7 use CuO and MnO2 as sintering metal oxides, respectively. Although lower resistivity can be obtained, the relative density is low, which makes it difficult to use for stable PVD DC magnetron sputtering coating.
[0071] In summary, in Examples 1-6 of the present invention, by doping with a specific sintering aid and controlling the sintering atmosphere and temperature regime, the modified ATO ceramic target material after sintering has excellent properties of high density and low resistivity, achieving a relative density of ≥97.8%, or even up to 99.2%; and a resistivity of ≤5.2×10 -3 Ω·cm, even up to 3.8×10 -3 Ω·cm. The doped and modified ATO ceramic target can be stably used in large-scale production of magnetron sputtering (PVD) coating, and its corrosion resistance and high temperature resistance can also be used in glass kilns and electrodes of new energy batteries.
[0072] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A modified ATO ceramic target, characterized in that: The raw material components include, by weight: 89-98 parts of tin oxide, 1-10 parts of antimony oxide, and 1-3 parts of doped oxide, wherein the doped oxide is at least one of ZnO, Bi2O3, TiO2, and Ta2O5.
2. The modified ATO ceramic target according to claim 1, characterized in that: The raw material components include, by weight: 94-98 parts of tin oxide, 1-7 parts of antimony oxide, and 1-3 parts of doped oxide.
3. The modified ATO ceramic target according to claim 1 or 2, characterized in that: The purity of the tin oxide is ≥99.99%; and / or the specific surface area of the tin oxide is 15-25m 2 / g; and / or, the particle size distribution of the tin oxide is D 50 ≤0.5μm, D max ≤5μm.
4. The modified ATO ceramic target according to claim 1 or 2, characterized in that: The purity of the doped oxide is ≥99.99%; and / or the specific surface area of the doped oxide is 15-25m 2 / g; and / or, the particle size distribution of the doped oxide is D 50 ≤2μm, D max ≤10μm.
5. A method for preparing a modified ATO ceramic target according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) weighing tin oxide, antimony oxide and doping oxide according to mass ratio, wet ball milling and spray drying to obtain a mixed powder; (2) isostatically pressing the mixed powder to obtain a target blank; (3) After degreasing the target blank, sintering it in an oxygen atmosphere to obtain the modified ATO ceramic target.
6. The method for preparing the modified ATO ceramic target according to claim 5, characterized in that: In step (1), the moisture content of the mixed powder is ≤1%.
7. The method for preparing the modified ATO ceramic target according to claim 5, characterized in that: In step (2), the isostatic pressing process conditions are: isostatic pressing at a pressure of 100-200 MPa for 30-60 minutes.
8. The method for preparing the modified ATO ceramic target according to claim 5, characterized in that: In step (3), the degreasing process conditions are: keeping at 600-650° C. for 2-3 hours; and / or, the degreasing is carried out in an air atmosphere.
9. The method for preparing the modified ATO ceramic target according to claim 5, characterized in that: In step (3), the sintering temperature regime is: firstly, the temperature is raised to 1150-1250°C at a rate of 0.4-0.6°C / min, and the heat preservation time is 6-8 hours; then, oxygen is introduced, and the temperature is raised to 1350-1400°C at a rate of 0.2-0.4°C / min, and the heat preservation time is 10-12 hours; finally, the oxygen introduction is stopped, and the temperature is lowered to room temperature at a rate of 0.5-1.5°C / min.
10. Use of the modified ATO ceramic target material according to any one of claims 1 to 4 in magnetron sputtering coating, glass kiln or battery.
Citation Information
Patent Citations
Tin Oxide Ceramic Sputtering Target And Method Of Producing It
CN102811971A
Tin oxide-based target material and preparation method thereof
CN116655372A
Target of tin - antimony oxide sintered compact, and manufacturing method therefor
JP2003073819A
Cited By
Multi-element synergetic doped ATO target material and preparation method thereof
CN120483707A
